2021
DOI: 10.3389/fmolb.2021.705133
|View full text |Cite
|
Sign up to set email alerts
|

Sialidase and Sialyltransferase Inhibitors: Targeting Pathogenicity and Disease

Abstract: Sialidases (SAs) and sialyltransferases (STs), the enzymes responsible for removing and adding sialic acid to other glycans, play essential roles in viruses, bacteria, parasites, and humans. Sialic acid is often the terminal sugar on glycans protruding from the cell surface in humans and is an important component for recognition and cell function. Pathogens have evolved to exploit this and use sialic acid to either “cloak” themselves, ensuring they remain undetected, or as a mechanism to enable release of viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 110 publications
0
19
0
1
Order By: Relevance
“…Moreover, limitations of methodological approaches need to be considered, such as missing environmental context for in vitro cell cultures or species differences for in vivo studies. Functional redundancy may exist between SiaTs, and while specific small-molecule SiaT inhibitors that bind and block select SiaTs may hold promise for therapeutic and diagnostic use [for recent reviews see (257)(258)(259)], combination strategies might be needed in a given context. However, the observation that SiaTs are responsible for the generation of glyco-immune checkpoints has reinvigorated ambitions of researchers to explore the role of individual SiaTs in cancer, which may pave the way for novel immune normalization (260), and more personalized, cancer immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, limitations of methodological approaches need to be considered, such as missing environmental context for in vitro cell cultures or species differences for in vivo studies. Functional redundancy may exist between SiaTs, and while specific small-molecule SiaT inhibitors that bind and block select SiaTs may hold promise for therapeutic and diagnostic use [for recent reviews see (257)(258)(259)], combination strategies might be needed in a given context. However, the observation that SiaTs are responsible for the generation of glyco-immune checkpoints has reinvigorated ambitions of researchers to explore the role of individual SiaTs in cancer, which may pave the way for novel immune normalization (260), and more personalized, cancer immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the potential off-target effects on the liver and kidney exhibited by the pan-inhibitor 3FAX-Neu5Ac, it has been suggested that for sialyltransferase inhibitors to proceed to clinical trials, they will need to be specific to individual enzymes [ 25 ]. However, as sialyltransferase enzymes are often membrane-bound proteins, this has led to difficulties in successfully crystallising the enzymes, and only a handful of human sialyltransferase structures exist [ 229 ]. These include ST6GAL1 [ 230 ], ST6GalNAC2 [ 231 ], and ST8SIA3 [ 232 ] and have enabled the development of a new series of carbamate-linked sialyltransferase inhibitors [ 233 ].…”
Section: Therapeutic Strategies To Inhibit Aberrant Sialylationmentioning
confidence: 99%
“…Amongst the diversity of glycans present in living organisms, N -acetylneuraminic acid (Neu5Ac, sialic acid) is typically found as a terminal unit of surface glycoconjugates and is crucial to various cellular recognition events in both physiological and pathological processes [ 1 ]. This distinctive negatively charged monosaccharide is the natural substrate for sialidases, which belong to different glycoside hydrolase (GH) families and play fundamental roles in the biology of humans, viruses, bacteria and parasitic protozoa by cleaving glycosidic linkages and releasing (or transferring) sialic acid from sialylated substrates [ 2 ]. In fact, sialidases have been associated with the pathogenesis of various diseases and the development of potent and selective inhibitors can serve as the basis for new therapeutics [ 3 ].…”
Section: Introductionmentioning
confidence: 99%